Efeito da aplicação de extrato de erva-mate (llex paraguariensis) assistido por ultrassom na estabilidade oxidativa de linguiça suína - Serafim, Rodolfo Angelo (2016)
The antioxidant properties of yerba mate has long been known and studied, the main reason is regarding its many therapeutic principles. Its phenolics content, main source of antioxidant agents, can also be applied in the industry for retarding the unwanted biochemical changes in the shelf-life of food. Therefore, this work is shown as an opportunity to demonstrate the potential of yerba mate extracts applied to pork sausages, a product which has as main limiting of its shelf-life expectancy the lipid oxidation. To obtain the extract was applied a factorial design by adding axial points, seeking for the best conditions of ultrasound extraction for increased antioxidant activity in response to free radical scavenging activity determined by DPPH and ABTS. The variables studied were temperature (22, 30, 50, 70 and 78 °C) and time (6, 10, 20, 30 and 34 min.). In the conditions of this study, the temperature was the only variable that showed, with 95% confidence level, positive influences significantly, both linear and quadratic, in the antioxidant activity of the yerba mate extracts. Thus, the following conditions were chosen in order to obtain the yerba mate extract: ultrasound bath for 10 minutes at 60 ° C. Then the extract was applied in fresh pork sausage in different concentrations of sodium erythorbate (0, 0.01 and 0.02%) and yerba mate extract (0, 0.03 and 0.06%). Accordingly, the yerba mate extract showed an improved ability to inhibit the oxidation of pork sausage when applied above 0.06% and lower concentrations of sodium erythorbate concentrations of 0.01% combined, in this study conditions. The consumer acceptance in the sensorial analysis was verified between two sausage formulations, both with the same concentration of sodium erythorbate, however just one of them was added yerba mate extract (0.03%). The test showed no significant difference between the assessment of color, flavor and global score, with acceptance levels above 70% for those attributes.